Pancasila as Philosophical Basis in Strengthening National Character in the Era of Globalization - Susilawati, Marietta D.; Indrawati, Etty; Shalom, Efraim Yehuda (West Science Law and Human Rights, 2025)
Pancasila as the philosophical basis has an important role in strengthening the character of the nation, especially in the challenging era of globalization. This research aims to examine how applying Pancasila values can be integrated into character education in higher education in Indonesia to face challenges in the era of globalization. This research aims to find out the application of Pancasila values in shaping the identity and character of the nation that needs to be lived by the Indonesian people, including the younger generation. Character cultivation is essential for all Indonesian people in the era of globalization. The values of Pancasila need to be instilled in the younger generation so that Indonesia becomes a strong nation in the face of globalization. This research uses qualitative methods. The approach to be used is to combine library research with field research. The material object is the education policy model that has been carried out by the College, and the formal object is the philosophy of Pancasila.